Political instability in Israel over the last decades – Causes and consequences - Erez Cohen (Cogent Social Sciences)
This article reviews the deterioration of government stability in Israel since the late 1990s and in the last three years in particular and examines the causes and consequences of this reality. The findings indicate several factors that have been contributing to government instability in Israel beginning from the late 1990s. One is the considerable heterogeneity typical of Israeli society, which encourages the establishment of many sectoral parties based on faith, country of origin, or some common interest. The second is related to cultural changes that derive from embracing a utilitarian worldview which has begun to spread throughout Israeli society and to leave its mark on the citizens’ voting patterns, and the third is related to the many possible options for dissolving the Knesset. These factors, together and separately, have led to an inability to form a stable government that has sufficient electoral power to lead long-term policy processes. Instead, government stability is eroding increasingly, politicians are developing a reasoning that is based on narrow interests and neglecting the values and ideologies for which they were chosen. All this in order to preserve their political survival, which has become their top goal, instead of promoting wide public interests.